Glycine and taurine equally prevent fatty livers from Kupffer cell-dependent injury: an in vivo microscopy study - Bruns, Helge; Watanpour, Ingo; Gebhard, Martha-Maria; Flechtenmacher, Christa; Galli, Uwe; Schulze-Bergkamen, Henning; Zorn, Markus; Büchler, Markus W.; Schemmer, Peter (Microcirculation, 2011)
Background: IRI still is a major problem in liver surgery due to warm ischemia and organ manipulation. Steatosis is not only induced by diabetes, hyperalimentation, alcohol and toxins, but also chemotherapy given before resection. Since steatotic livers are prone to Kupffer cell-dependent IRI, protection of steatotic livers is of special interest. This study was designed to compare the effect of taurine and glycine on IRI in steatotic livers. Materials and Methods: Steatosis was induced with ethanol (7 g/kg b.w.; p.o.) in female SD rats. Ten minutes after inactivation of Kupffer cells with taurine or glycine (300 mM; i.v.), left liver lobes underwent 60 minutes of warm ischemia. Controls received the same volume of valine (300 mM; i.v.) or normal saline. After reperfusion, white blood cell-endothelial interactions and latex-bead phagocytosis by Kupffer cells were investigated. Liver enzymes were measured to estimate injury. For statistical analysis, ANOVA and Student’s t-test were used. Results: Glycine and taurine significantly decreased leukocyte- and platelet-endothelium interactions and latex-bead phagocytosis (p < 0.05). Liver enzymes were significantly lower after glycine and taurine (p < 0.05). Conclusions: This study shows that preconditioning with taurine or glycine is equally effective in preventing injury to fatty livers most likely via Kupffer cell-dependent mechanisms.
First published: 22 December 2010
Gesehen am 24.06.2022